In-situ observations of the magnetothermodynamic evolution of electron-only reconnection - D. S. Payne; M. Swisdak; J. P. Eastwood; J. F. Drake; P. S. Pyakurel; J. R. Shuster (Communications Physics, 2025)
Abstract Field-particle energy exchange is important to the magnetic reconnection process, but uncertainties regarding the time evolution of this exchange remain. We investigate the temporal dynamics of field-particle energy exchange during magnetic reconnection, using Magnetospheric Multiscale mission observations of an electron-only reconnection event in the magnetosheath. The electron energy is in local minimum at the x-line due to a density depletion, while the magnetic energy is in local maximum due to a guide field enhancement. The electromagnetic energy transport comes almost entirely from guide field contributions and is confined within the reconnection plane, while the most significant contribution to electron energy transport is independent of the drift velocity with additional out-of-plane signatures. Multi-spacecraft analysis suggests that the guide field energy is decreasing while the electron density is increasing, both evolving such that the system is moving toward a more uniform distribution of magnetic and thermal energy.